On the use of a split Hopkinson pressure bar in structural geology: High strain rate deformation of Seeberger sandstone and Carrara marble under uniaxial compression. (April 2017) - Zwiessler, Ruprecht; Kenkmann, Thomas; Poelchau, Michael H.; Nau, Siegfried; Hess, Sebastian
Abstract: There is increasing evidence that seismogenic fractures can propagate faster than the shear wave velocity of the surrounding rocks. Strain rates within the tip region of such super-shear earthquake ruptures can reach deformation conditions similar to impact processes, resulting in rock pulverization. The physical response of brittle rocks at high strain rates changes dramatically with respect to quasi-static conditions. Rocks become stiffer and their strength increases. A measure for the dynamic behavior of a rock and its strain dependency is the dynamic increase factor ( DIF) which is the ratio of the dynamic compressive strength to the quasi-static uniaxial compressive strength. To investigate deformation in the high strain rate regime experimentally, we introduce the split Hopkinson pressure bar technology to the structural geology community, a method that is frequently used by rock and impact engineers. We measure the stress-strain response of homogeneous, fine-grained Seeberger sandstone and Carrara marble in uniaxial compression at strain rates ranging from 10 +1 to 10 +2 s −1 with respect to tangent modulus and dynamic uniaxial compressive strength. We present full stress-strain response curves of Seeberger sandstone and Carrara marble at high strain rates and an evaluation method to determine representative rates of deformation. Results indicate a rate-dependent elastic behavior of Carrara marble where an average increase of ∼18% could be observed at high strain rates of about 100 s −1 . DIF reaches a factor of 2.2–2.4. Seeberger sandstone does not have a rate-dependent linear stress-strain response at high strain rates. Its DIF was found to be about 1.6–1.7 at rates of 100 s −1 . The onset of dynamic behavior is accompanied with changes in the fracture pattern from single to multiple fractures to pervasive pulverization for increasing rates of deformation. Seismogenic shear zones and their associated fragment-size spectra should be carefully revisited in the light of dynamic deformation. Highlights: Rock failure at fast strain rate is studied with a split Hopkinson pressure bar. Stress, strain, and strain rate are precisely analyzed in a new evaluation method. Response at high strain rates shows increasing stiffness and rock strength. Dynamic elastic properties and rock strength are given for sandstone and marble. Deformation conditions in large seismogenic fault zones can be reconstructed.